Fourth order computational spline method for two-parameter singularly perturbed boundary value problem - Kambampati, Satyanarayana; Emineni, Siva Prasad; Reddy M., Chenna; Kolloju, Phaneendra (Zielona Góra: Uniwersytet Zielonogórski)
The current research work considers a two-parameter singularly perturbed two-point boundary value problem. Here, we suggest a computational scheme derived by using an exponential spline for the numerical solution of the problem on a uniform mesh. The proposed numerical scheme is analyzed for convergence and an accuracy of O(h4) is achieved. Numerical experiments are considered to validate the efficiency of the spline method, and compared comparison with the existing method to prove the superiority of the proposed scheme.
Keywords: spline; two-parameter singularly perturbed two-point boundary value problem; dual layer; characteristic equation; convergence